The Brave new world of online digital home entertainment. - But, Jason (IEEE Communications magazine)
The emergence of widespread broadband home Internet connectivity is leading to a change in patterns of home user online behavior. Innovative networked applications (e.g., online multimedia and gaming) are making their mark. Will the next killer Internet applications be new forms of online digital home entertainment? Can the Internet support a widespread explosion in the use of such applications? In this article we explore potential problems in running interactive multimedia and game applications over existing Internet and home access network infrastructures. We also discuss the issues both network and application developers should consider when designing new Internet entertainment applications such that widespread usage becomes a possibility.